Finite Element Simulation of the Dynamic Pressure Distribution of A Typical Compression Sports Bra During Wearing (Journal of Fiber Bioengineering and Informatics, 2020)
In order to study the pressure comfort of women in the process of wearing a typical compression sports bra, a simulation model was established using the finite element method to simulate women wear a typical compression sports bra, and the contact analysis of the human chest and the sports bra during the wearing process, Obtain the dynamic pressure changes during the wearing of the sports bra. In order to obtain a more accurate pressure value, the human body model is simplified into four layers, namely skin layer, fat layer, muscle layer, and bone layer. The skin layer and sports bra model are obtained through the method of reverse modeling, and then through the deletion calculation Generate adipose layer, muscle layer, bone layer and breast structure. The simulation results show: the pressure distribution between the sports bra and the human body: the pressure value at the human breast is 0.67 Kpa-1.87 Kpa, the shoulder pressure is 1.87 Kpa-3.68 Kpa, and the pressure at the bending part is 1.13 Kpa-1.74 Kpa. The pressure of the back shoulder strap and the part that is in contact with the human body is relatively uniform, ranging from 0.54 Kpa-1.14 Kpa. The experimental data in the literature proves that the finite element model is effective and reasonable.